Mortality from chronic respiratory disease in Brazil: time trend and forecasts - Marcio Sacramento de Oliveira; Elisa Hypólito Montovani; Maria de Fátima Ebole de Santana; Antonio Carlos Monteiro Ponce de Leon; Márcio Candeias Marques (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the time trend of monthly mortality rates from chronic respiratory diseases in Brazil from 1996 to 2017, with forecasts for 2022, besides analyzing the possibility of achieving the goal of the Plano de Ações Estratégicas para o Enfrentamento das Doenças Crônicas Não Transmissíveis no Brasil (Strategic Action Plan to Tackle Chronic Noncommunicable Diseases in Brazil) from 2011 to 2022. METHODS This is an ecological study that uses data from Sistema de Informações sobre Mortalidade (SIM - Mortality Information System), Sistema de Informações Demográficas e Socioeconômicas (Demographic and Socioeconomic Information System) and Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD Contínua - Continuous National Household Sample Survey). We established the age range between 30 and 69 years old and the evolution of the rates over time was made by autoregressive integrated moving average models in R statistical tool. RESULTS Premature mortality rates from chronic respiratory diseases are decreasing in Brazil as a whole, mostly in state capitals. There is also a trend to reach the Ministry of Health's goal in most of the country. For capitals that tend not to reach the goal, there is an association between mortality and social indicators, healthcare network and frequency of smoking. CONCLUSION This study intends to improve planning of the public health system for the control of chronic respiratory diseases.